EFFECT OF CREDIT RISK MANAGEMENT ON THE PROFITABILITY OF NIGERIAN BANKS - Blessing Ebere, Chikwem,; Chinedum Nwezeaku , Nathaniel; Ejiogu, Chris-; Gloria, Uzoamaka (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2023)
This study investigated the effect of credit risk management on the profitability of Nigerian banks from 2006-2020. Three banks were sampled (First Bank Nig Plc (FBN), Zenith Bank Plc (ZBN) and First City Monument Bank Plc (FCMB)). The study specifically determined the effect of non-performing loan to total loan ratio (NPR), non-performing loan to total deposit ratio (NDR), capital adequacy ratio (CAR), leverage ratio (LEV) and firm size (FSZ) on profitability of banks measured by Return On Assets (ROA) and Return On Equity (ROE). The study utilized secondary data sourced from annual reports and accounts of the selected banks for the period of the research work. The study employed multiple regression of OLS (Ordinary Least Square) and estimation obtained from E-views version 9 to determine the statistical relationship between credit risk management and profitability of banks in Nigeria. The finding revealed a positive insignificant relationship between NLR and profitability of banks, CAR and FSZ showed a negative insignificant relationship with profitability, LEV revealed a positive significant relationship in only ROE of Zenith Bank and First City Monument Bank while NDR revealed a negative insignificant relationship in First Bank and Zenith Bank only. Based on the above findings, this study recommended that the Central Bank of Nigeria, for policy purposes should frequently assess the lending habit of banks in Nigeria